Liposome collapse resulting from an allosteric interaction between 2, 6-dimethyl-β-cyclodextrins and lipids1. Issue 95 (15th October 2015) - Ikeda, Atsushi; Iwata, Noboru; Hino, Shodai; Mae, Tomoya; Tsuchiya, Yuki; Sugikawa, Kouta; Hirao, Takehiro; Haino, Takeharu; Ohara, Kazuaki; Yamaguchi, Kentaro
<x xml:space="preserve">Abstract</x> The addition of a large excess of heptakis(2, 6-di-O-methyl)-β-cyclodextrin (DMe-β-CDx) led to the collapse of several liposomes via the formation of water-soluble lipid–DMe-β-CDx complex with allosteric interactions.